Jodoh di Ujung Jempol: Tinder sebagai Ruang Jejaring Baru - Amelinda Pandu Kusumaningtyas; Azinuddin Ikram Hakim (Universitas Trunojoyo Madura, 2019)
Tinder has become part of youth life in Indonesia and challenging the conventional and traditional way of courtship. The increasing of communication technology has an impact to change the way we communicate each other, a lifestyle, and a values in romance relationship. Tinder is one of products from the technology of media in the network societies. This case study research was conducted to understand how Tinder change Indonesian youth’s courtship experience. We interviewed 3 young Tinder users from different background with diverse experience. Through this study we found five interesting findings: (1) Tinder has contributed to the decrease of parents role in courtship, (2) Tinder has simplified the conceptnof relationship, (3) Ttinder is a safe space for marginalized youth to express themselves, (4) Tinder is a part of arena for network society, and (5) Tinder is surrounded with various stigma from general public.